Engineered Hybrid Nanoparticles for On-Demand Diagnostics and Therapeutics - Nguyen, Kim Truc (2016)
Together with the simultaneous development of nanomaterials and molecular biology, the bionano interface brings about various applications of hybrid nanoparticles in nanomedicine. The hybrid nanoparticles not only present properties of the individual components but also show synergistic effects for specialized applications. Thus, the development of advanced hybrid nanoparticles for targeted and on-demand diagnostics and therapeutics of diseases has rapidly become a hot research topic in nanomedicine. The research focus is to fabricate novel classes of programmable hybrid nanoparticles that are precisely engineered to maximize drug concentrations in diseased cells, leading to enhanced efficacy and reduced side effects of chemotherapy for the disease treatment. In particular, the hybrid nanoparticle platforms can simultaneously target diseased cells, enable the location to be imaged by optical methods, and release therapeutic drugs to the diseased cells by command.